Digital opportunities to connect and complain – the use of Facebook in small animal practice. Issue 1 (28th February 2022) - Springer, Svenja; Lund, Thomas Bøker; Sandøe, Peter; Corr, Sandra A.; Kristensen, Annemarie T.; Grimm, Herwig
Abstract: Background: Social media is increasingly used in small animal practice, enabling veterinarians to connect with clients and promote their business online. It can also be used by clients to quickly distribute complaints via online communities. Material/methods: Using a questionnaire study we investigated Austrian, Danish and UK veterinarians' attitudes towards Facebook, the contents of clients' online complaints and how they were handled by veterinarians ( N  = 648). Results: In Denmark and the UK, around 90% of practices had a Facebook page, in contrast to 40% of Austrian practices. Most Danish and UK veterinarians agreed that the use of Facebook was relevant and expected by clients. Agreement was lower among Austrian veterinarians, probably reflecting the lower uptake of social media there. In particular, younger veterinarians and those who actively used Facebook for the practice, could see benefits. In all three countries, we found that clients most frequently complained about treatment costs. Most veterinarians preferred to actively deal with clients' complaints, either replying online or discussing them directly. Conclusions: We recommend future research focusing on veterinarians' personal use of social media and on clients' use of and attitudes towards social media in the veterinary context.